Graphite negative electrode material and preparation method thereof, negative electrode plate, battery and power-related equipment

By adopting directionally arranged secondary particle structures and magnetic solid particles in graphite negative electrode materials, the problems of large tortuosity and long Li+ transfer paths of the graphite negative electrode materials are solved, and a lithium-ion battery with high magnification performance is achieved.

CN119890261APending Publication Date: 2025-04-25SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016780.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The internal tortuosity of the existing graphite negative electrode particles is relatively large, and the Li+ transmission path is longer, which affects the rate performance.

Method used

The secondary particles composed of multiple graphite particles are used, and the surface of the graphite particles is coated with a hard carbon coating layer, and the graphite particles are arranged in a directional manner through an external magnetic field, increasing magnetic solid particles to improve the directional arrangement effect.

Benefits of technology

Effectively shorten the transmission path of lithium ions, reduce tortuosity, improve the ion transfer rate and diversity of transmission channels, and enable the battery to have high magnification performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890261A_ABST
    Figure CN119890261A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode material and a preparation method thereof, a negative electrode plate, a battery and power-related equipment, and relates to the technical field of new energy. The graphite negative electrode material provided by the invention comprises secondary particles composed of a plurality of graphite particles, the surfaces of the graphite particles are coated with hard carbon coating layers, the plurality of graphite particles are adhered together through the hard carbon coating layers, and the plurality of graphite particles in the secondary particles are in a directional arrangement morphology. Although the secondary particles of the electrode plate prepared from the electrode plate are still randomly and disorderly arranged, the directional arrangement degree of the graphite particles in the secondary particles is obviously improved, namely, the arrangement orientation of the internal particles tends to be consistent or the arrangement order degree is improved, so that the transmission path of lithium ions can be effectively shortened, namely, the condition that Li < + > in an electrolyte reaches the surface of an active substance is shortened, and the service life of the electrode plate is prolonged. And the distance to the reaction center is reduced, the tortuosity is reduced, and the lithium ion battery prepared from the graphite negative electrode material has the characteristics of high ion transfer rate and multiple transfer channels, so that the lithium ion battery prepared from the graphite negative electrode material has the performance characteristic of high magnification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a graphite negative electrode material and a preparation method thereof, a negative electrode sheet, a battery and electrical equipment. Background Art

[0002] With the continuous development of the new energy vehicle industry, the power battery industry has continued to progress, and the requirements for battery fast charging performance have continued to increase. Coating and granulation processes are effective means to improve the rate performance of graphite negative electrode materials. Resin materials can form a hard carbon layer after carbonization as coating materials. Hard carbon is isotropic and has a larger interlayer spacing than graphite. During the charging process, lithium ions diffuse quickly and have good rate performance. However, the internal tortuosity of existing graphite negative electrode material particles is still large, and Li + The transfer path is longer, which affects the rate performance. Summary of the invention

[0003] The purpose of this application is to provide a graphite negative electrode material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device, aiming to solve the problem that the internal tortuosity of the existing graphite negative electrode material particles is still relatively large. + The transfer path is long, which affects the rate performance.

[0004] To achieve the above objectives, the present application provides a graphite negative electrode material, including multiple secondary particles, wherein the secondary particles are composed of multiple graphite particles, the surface of the graphite particles is coated with a hard carbon coating layer, the multiple graphite particles are adhered together by the hard carbon coating layer, and the multiple graphite particles are in a directional arrangement morphology.

[0005] In some embodiments, the surface of the graphite particles is further coated with magnetic solid particles, and the magnetic solid particles are used to align the plurality of graphite particles in a directional manner under the action of an external magnetic field.

[0006] In some embodiments, at least one of the following conditions is met: A. The mass of the hard carbon coating layer accounts for 0.1% to 10% of the mass of the secondary particles; Preferably, the mass of the hard carbon coating layer accounts for 0.1%-3% of the mass of the secondary particles; B. The particle size D50 of the graphite particles is 3-20 μm; Preferably, the particle size D50 of the graphite particles is 5-10 μm; C. The particle size D50 of the secondary particles is 5-30 μm; Preferably, the particle size D50 of the secondary particles is 8-18 μm; D. The graphite particles are selected from one or more combinations of natural graphite, artificial graphite, expanded graphite, oxidized graphite and microcrystalline graphite.

[0007] In some embodiments, at least one of the following conditions is met: A. The mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~500*10 -3 %; Preferably, the mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~200*10 -3 %; B. The magnetic solid particles are selected from one or more combinations of iron powder, ferroferric oxide, nickel magnetic beads, ferrous oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

[0008] The present application also provides a method for preparing a graphite negative electrode material, comprising: Mixing graphite particles, water-soluble resin material, and magnetic fluid to obtain slurry; The slurry is spray-dried and an external magnetic field is applied during atomization to obtain a granulated product; The granulated product is carbonized to obtain the graphite negative electrode material.

[0009] In some embodiments, at least one of the following conditions is met: A. The water-soluble resin material is selected from one or more combinations of phenolic resin, epoxy resin, furfural resin, acrylic resin, polyurethane resin, acrylic-polyurethane copolymer, furan resin, polyvinyl alcohol, chitosan, cellulose, styrene-butadiene rubber, and glucose; B. The solid content of the solution of the water-soluble resin material is 0.1% to 90%; C. The mass of the water-soluble resin material accounts for 0.1%-20% of the graphite negative electrode material; D. The magnetic fluid is a water-based magnetic fluid; E. The magnetic fluid is a water-based magnetic fluid, and the solid content of the water-based magnetic fluid is 0.001% to 50%; F. The magnetic fluid is a water-based magnetic fluid, and the particle size of the magnetic solid particles in the water-based magnetic fluid is ≤100nm; G. The magnetic fluid is a water-based magnetic fluid, and the magnetic solid particles in the water-based magnetic fluid are selected from a combination of one or more of iron powder, ferroferric oxide, nickel magnetic beads, ferric oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

[0010] In some embodiments, at least one of the following conditions is met: A. The graphite particles, the water-soluble resin material and the magnetic fluid are mixed to obtain a slurry, comprising: The graphite particles and the water-soluble resin material are first mixed and then a magnetic fluid is added to perform a second mixing to obtain the slurry; B. When condition A is met, the stirring speed of the first mixing is 200 r / min to 400 r / min, and the stirring time is 40 to 180 min; C. When condition A is met, the stirring speed of the second mixing is 400 r / min to 2000 r / min, and the stirring time is 40 to 180 min; D. spray drying the slurry, further comprising: applying ultrasound during drying; E. The carbonization temperature is 400°C to 1300°C; F. The carbonization time is 2 to 15 hours.

[0011] The present application also provides a negative electrode sheet, comprising the above-mentioned graphite negative electrode material.

[0012] The present application also provides a battery, comprising the above-mentioned negative electrode sheet.

[0013] The present application also provides an electrical device, comprising the above-mentioned battery.

[0014] Compared with the prior art, the beneficial effects of this application include: The graphite negative electrode material provided in the present application includes secondary particles composed of multiple graphite particles, the surface of the graphite particles is coated with a hard carbon coating layer, and the multiple graphite particles inside the secondary particles present a directional arrangement morphology. Although the arrangement between the active material particles of the electrode sheet prepared by using the secondary particles is still random and disordered, the degree of directional arrangement of the particles inside the active material particles is significantly improved, that is, the arrangement of the internal particles tends to be consistent or the order of the arrangement is improved (such as Figure 2 ), which can effectively shorten the transmission path of lithium ions, that is, shorten the Li + The distance to the surface of the active substance is shortened, thereby shortening the distance to the reaction center and reducing the tortuosity (e.g. Figure 3 ), with the characteristics of fast ion transfer rate and multiple transfer channels, the lithium-ion battery prepared by the graphite negative electrode material has high-rate performance characteristics. At the same time, the degree of directional arrangement of graphite particles inside the secondary particles is improved, that is, the order of the internal particle arrangement direction is improved, which can increase the tap density of the material and help to improve the energy density of the electrode.

[0015] The arrangement of graphite particles inside the secondary particles prepared without adding magnetic fluid is random and disordered (e.g. Figure 4 ), the tortuosity could not be reduced after it was used to prepare the electrode (such as Figure 5 ), the transmission path of lithium ions is long, so the lithium ion transfer rate is limited.

[0016] The preparation method of the graphite negative electrode material provided in the present application comprises preparing a spray-dried slurry containing graphite particles and a resin material, and adding a magnetic fluid to the slurry. By adding a magnetic field outside the atomizer, the magnetic solid particles on the surface of the graphite particles are oriented under the action of the external magnetic field. The graphite particles in the internal structure of the secondary particles formed by the spray drying process present a directional arrangement morphology. After carbonization, the resin coating layer forms a hard carbon structure, and a granulated product having a hard carbon coating layer and magnetic solid particles is prepared.

[0017] The negative electrode sheet, battery and electrical equipment provided by the present application have excellent electrochemical performance and high rate performance due to the use of the graphite negative electrode material of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0019] Figure 1 A schematic diagram of a process for preparing a graphite negative electrode material of the present application; Figure 2 A schematic diagram of the preparation process of the graphite negative electrode material with an internal directional arrangement structure of the present application; Figure 3 The Li in the electrode prepared from the graphite negative electrode material of this application + Model diagram of the transfer; Figure 4 A schematic diagram of the preparation process of a graphite negative electrode material with a non-directional arrangement structure in the prior art; Figure 5 Li in the electrode prepared from the graphite negative electrode material of the prior art + Model diagram of the transfer; Figure 6 This is a SEM image of the graphite negative electrode material of Example 6 of the present application; Figure 7 This is a SEM image of the graphite negative electrode material of Comparative Example 1 of the present application; Figure 8 This is a particle size distribution diagram of the graphite negative electrode material of Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0020] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0021] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0022] The present application provides a graphite negative electrode material, comprising a plurality of secondary particles, wherein the secondary particles are composed of a plurality of graphite particles, the surface of the graphite particles is coated with a hard carbon coating layer, the plurality of graphite particles are adhered together by the hard carbon coating layer, and the plurality of graphite particles are in a directional arrangement morphology.

[0023] The graphite negative electrode material provided in the present application includes secondary particles composed of multiple graphite particles, the surface of the graphite particles is coated with a hard carbon coating layer, and the multiple graphite particles inside the secondary particles present a directional arrangement morphology. Although the arrangement between the active material particles of the electrode sheet prepared by using the secondary particles is still random and disordered, the degree of directional arrangement of the particles inside the active material particles is significantly improved, that is, the arrangement of the internal particles tends to be consistent or the order of the arrangement is improved (such as Figure 2 ), which can effectively shorten the transmission path of lithium ions, that is, shorten the Li + The distance to the surface of the active substance is shortened, thereby shortening the distance to the reaction center and reducing the tortuosity (e.g. Figure 3 ), with the characteristics of fast ion transfer rate and multiple transfer channels, the lithium-ion battery prepared by the graphite negative electrode material has high-rate performance characteristics. At the same time, the degree of directional arrangement of graphite particles inside the secondary particles is improved, that is, the order of the internal particle arrangement direction is improved, which can increase the tap density of the material and help to improve the energy density of the electrode.

[0024] The arrangement of graphite particles inside the secondary particles prepared without adding magnetic fluid is random and disordered (e.g. Figure 4 ), the tortuosity could not be reduced after it was used to prepare the electrode (such as Figure 5 ), the transmission path of lithium ions is long, so the lithium ion transfer rate is limited.

[0025] In some embodiments, the surface of the graphite particles is further coated with magnetic solid particles, and the magnetic solid particles are used to align the plurality of graphite particles in a directional manner under the action of an external magnetic field.

[0026] In some embodiments, the mass of the hard carbon coating layer accounts for 0.1% to 10% of the mass of the secondary particles, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or any value between 0.1% and 10%.

[0027] Preferably, the mass of the hard carbon coating layer accounts for 0.1%-3% of the mass of the secondary particles.

[0028] In some embodiments, the mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~500*10 -3 %, for example, it can be 0.1*10 -3 %,10*10 -3 %,50*10 -3 %,100*10 -3 %,150*10 -3 %,200*10 -3 %,250*10 -3 %,300*10 -3 %,350*10 -3 %,400*10 -3 %,450*10 -3 %,500*10 -3 % or 0.1*10 -3 %~500*10 -3 Any value between %.

[0029] Preferably, the mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~200*10 -3 %.

[0030] In some embodiments, the particle size D50 of the graphite particles is 3~20μm, for example, it can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value between 3~20μm.

[0031] Preferably, the particle size D50 of the graphite particles is 5-10 μm.

[0032] In some embodiments, the particle size D50 of the secondary particles is 5~30μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 22μm, 25μm, 30μm or any value between 5~30μm.

[0033] Preferably, the particle size D50 of the secondary particles is 8-18 μm.

[0034] In some embodiments, the graphite particles are selected from a combination of one or more of natural graphite, artificial graphite, expanded graphite, oxidized graphite, and microcrystalline graphite.

[0035] In some embodiments, the magnetic solid particles are selected from a combination of one or more of iron powder, ferroferric oxide, nickel magnetic beads, ferrous oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

[0036] This application also provides a method for preparing a graphite negative electrode material. Figure 1 ,include: S100: mixing graphite particles, water-soluble resin material and magnetic fluid to obtain slurry; S200: spray drying the slurry, applying an external magnetic field during atomization to obtain a granulated product; S300: Carbonizing the granulated product to obtain a graphite negative electrode material.

[0037] The preparation method of the graphite negative electrode material provided in the present application comprises preparing a spray-dried slurry containing graphite particles and a resin material, and adding a magnetic fluid to the slurry. By adding a magnetic field outside the atomizer, the magnetic solid particles on the surface of the graphite particles are oriented under the action of the external magnetic field. The graphite particles in the internal structure of the secondary particles formed by the spray drying process present a directional arrangement morphology. After carbonization, the resin coating layer forms a hard carbon structure, thereby preparing a graphite negative electrode material having a hard carbon coating layer and magnetic solid particles.

[0038] Among them, magnetic fluid, also known as magnetic liquid, ferromagnetic fluid or magnetic liquid, is a new type of functional material. It has both the fluidity of liquid and the magnetism of solid magnetic material. It is a stable colloidal liquid mixed with magnetic solid particles with a diameter of nanometers, base carrier liquid and surfactant. The fluid has no magnetic attraction when static, and only exhibits magnetism when an external magnetic field is applied.

[0039] In some embodiments, the water-soluble resin material in step S100 is selected from one or more combinations of phenolic resin, epoxy resin, furfural resin, acrylic resin, polyurethane resin, acrylic-polyurethane copolymer, furan resin, polyvinyl alcohol, chitosan, cellulose, styrene-butadiene rubber, and glucose.

[0040] In some embodiments, the solid content of the solution of the water-soluble resin material in step S100 is 0.1%~90%, for example, it can be 0.1%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value between 0.1% and 90%.

[0041] In some embodiments, the mass of the water-soluble resin material in step S100 accounts for 0.1%-20% of the graphite negative electrode material, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any value between 0.1%-20%.

[0042] In some embodiments, the magnetic fluid in step S100 is a water-based magnetic fluid; the solid content of the water-based magnetic fluid is 0.001%~50%, for example, it can be 0.001%, 0.01%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 30%, 40%, 50% or any value between 0.001%-50%.

[0043] In some embodiments, the particle size of the magnetic solid particles in the water-based magnetic fluid is ≤100 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any value ≤100 nm. In some embodiments, the magnetic solid particles in the water-based magnetic fluid are selected from a combination of one or more of iron powder, ferroferric oxide, nickel magnetic beads, ferric oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

[0044] In some embodiments, in step S100, graphite particles, water-soluble resin material, and magnetic fluid are mixed to obtain a slurry, including: The graphite particles and the water-soluble resin material are first mixed, and then a magnetic fluid is added to perform a second mixing to obtain the slurry.

[0045] The stirring speed of the first mixing is 200 r / min~400 r / min, and the stirring time is 40~180 min; the stirring speed of the second mixing is 400 r / min~2000 r / min, and the stirring time is 40~180 min.

[0046] In some embodiments, the spray drying in step S200 is an efficient drying technology that can atomize liquid feed into fine droplets and dry these droplets by hot air flow to remove moisture, and finally obtain a powder or granular product. Spray drying granulation equipment is an industrial machine that realizes this process, which includes the following key components: a spray system (such as an atomizer), a drying tower, a hot air flow, and a collection system. The slurry is pumped into the atomizer nozzle, where it is atomized into fine droplets and enters the drying tower, where it is quickly dried by the hot air flow, and the dried powder is collected by the collection system, usually using centrifugal force with a cyclone separator or a bag filter.

[0047] The external magnetic field can be applied, for example, by electromagnetic devices arranged on both sides of the atomizer nozzle. The size of the external magnetic field is not limited, and any size of the external magnetic field can be used as long as the magnetic solid particles can be moved and oriented under the action of the external magnetic field. The size of the external magnetic field is proportional to the slurry processing amount. The electromagnetic device can control the size of the external magnetic field by adjusting the current frequency, for example, the current frequency for controlling the magnetic field size can be 5-100 Hz.

[0048] In some embodiments, the spray drying of the slurry in step S200 further includes: applying ultrasound during drying. The ultrasound can be applied, for example, by an ultrasound device disposed on the wall of a drying tower, the magnitude of the ultrasound is proportional to the amount of slurry processed, and the ultrasound device can control the magnitude of the ultrasound by adjusting the current frequency. For example, the current frequency for controlling the magnitude of the ultrasound can be 5-50 Hz.

[0049] In some embodiments, the carbonization temperature in step S300 is 400°C~1300°C, for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C or any value between 400°C~1300°C; the carbonization time is 2~15 hours, for example, it can be 2 hours, 3 hours, 5 hours, 7 hours, 8 hours, 10 hours, 12 hours, 15 hours or any value between 2~15 hours.

[0050] This application also provides a negative electrode sheet, see Figure 2 and Figure 3 , including the above-mentioned graphite negative electrode material.

[0051] Compared to Figure 4 and Figure 5The electrode prepared by the graphite negative electrode material of the prior art, the multiple graphite particles inside the secondary particles of the graphite negative electrode material of the present application present a directional arrangement morphology, and although the arrangement between the active material particles of the electrode sheet prepared by using it is still random and disordered, the degree of directional arrangement of the graphite particles inside the active material particles is significantly improved, that is, the arrangement direction of the internal particles tends to be consistent or the order of the arrangement is improved, which can effectively shorten the transmission path of lithium ions, that is, shorten the Li in the electrolyte. + The distance to the surface of the active material and then to the reaction center reduces the tortuosity, and has the characteristics of fast ion transfer rate and multiple transfer channels, so that the negative electrode sheet prepared by this graphite negative electrode material has high-rate performance characteristics.

[0052] The present application also provides a battery, comprising the above-mentioned negative electrode sheet.

[0053] The present application also provides an electrical device, comprising the above-mentioned battery.

[0054] The battery and electrical equipment provided in the present application have excellent electrochemical performance and high rate performance due to the use of the graphite negative electrode material of the present application.

[0055] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0056] Example 1 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 0.1 g of magnetic fluid with a solid content of 1%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0057] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0058] The prepared granulated product is added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0059] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 1 accounts for 1% of the mass of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 1*10 of the mass of the secondary particles with the hard carbon coating layer. -3 %.

[0060] Example 2 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 1 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0061] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0062] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0063] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 2 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 50*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0064] Example 3 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 0.8 g of magnetic fluid with a solid content of 10%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0065] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0066] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0067] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 3 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 80*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0068] Example 4 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 1 g of magnetic fluid with a solid content of 10%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0069] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0070] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0071] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 4 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 100*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0072] Example 5 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 0.75 g of magnetic fluid with a solid content of 20%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0073] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0074] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0075] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 5 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0076] Example 6 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 1 g of magnetic fluid with a solid content of 20%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0077] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0078] The prepared granulated product was added to a high sand kiln for carbonization at a carbonization temperature of 1150°C for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance. The SEM image of the graphite negative electrode material of Example 6 is shown in FIG. Figure 6 shown.

[0079] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 6 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 200*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0080] Example 7 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 1.75 g of magnetic fluid with a solid content of 20%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0081] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0082] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0083] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 7 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 350*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0084] Example 8 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 1 g of magnetic fluid with a solid content of 45%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0085] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0086] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0087] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 8 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 450*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0088] Example 9 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99.5g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 1% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0089] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0090] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0091] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 9 accounts for 0.5% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0092] Example 10 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 98.5g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 3% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0093] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0094] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0095] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 10 accounts for 1.5% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0096] Embodiment 11 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 97g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 6% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0097] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0098] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0099] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 11 accounts for 3% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0100] Example 12 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 95g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 10% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0101] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0102] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0103] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 12 accounts for 5% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0104] Embodiment 13 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 92g of artificial graphite particles were added to 100g of phenolic resin solution with a solid content of 16% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0105] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0106] The prepared granulated product is added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain a graphite negative electrode material with high rate performance.

[0107] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 13 accounts for 8% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0108] Embodiment 14 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g of microcrystalline graphite particles were added to 100g of phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0109] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0110] The prepared granulated product is added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Example 14.

[0111] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 14 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0112] Embodiment 15 This embodiment provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99g natural graphite particles were added to 100g phenolic resin solution with a solid content of 2% and a residual carbon content of 50%, and stirred thoroughly at a stirring speed of 350r / min for 90min. -3 g of ferroferric oxide nanoparticle magnetic fluid (i.e., 3 g of magnetic fluid with a solid content of 5%) was added to the above mixture, and the mixture was fully mixed at a stirring speed of 1500 r / min for 180 min to obtain a slurry.

[0113] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field. The current frequency of the magnetic field device is 15 Hz, ultrasound is applied to the wall of the drying tower and the current frequency is 10 Hz, and the granulated product is obtained through the spray drying process.

[0114] The prepared granulated product is added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Example 15.

[0115] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Example 15 accounts for 1% of the secondary particles with the hard carbon coating layer, and the mass of the magnetic solid particles accounts for 150*10% of the secondary particles with the hard carbon coating layer. -3 %.

[0116] Example 16 This embodiment provides a graphite negative electrode material, and the preparation method thereof is different from that of embodiment 6 in that: the slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of an external magnetic field, the current frequency of the magnetic field device is 50 Hz, ultrasound is applied to the tower wall of the drying tower and the current frequency is 10 Hz, and a granulated product is obtained through a spray drying process. The remaining method steps and the quality of the hard carbon coating layer of the obtained graphite negative electrode material and the quality of the magnetic solid particles are the same as those of embodiment 6 and are not repeated here.

[0117] Embodiment 17 This embodiment provides a graphite negative electrode material, and its preparation method is different from that of embodiment 6 in that: The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of the external magnetic field. The current frequency of the magnetic field device is 90 Hz. Ultrasound is applied to the tower wall of the drying tower and the current frequency is 10 Hz. The granulated product is obtained by the spray drying process. The remaining method steps and the mass of the hard carbon coating layer of the obtained graphite negative electrode material and the mass of the magnetic solid particles are the same as those in Example 6 and are not repeated here.

[0118] Embodiment 18 This embodiment provides a graphite negative electrode material, and its preparation method is different from that of embodiment 6 in that: The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of the external magnetic field, the current frequency of the magnetic field device is 15 Hz, the tower wall of the drying tower is ultrasonically applied and the current frequency is 25 Hz, and the granulated product is obtained by the spray drying process. The remaining method steps and the mass of the hard carbon coating layer of the obtained graphite negative electrode material and the mass of the magnetic solid particles are the same as those in Example 6 and are not repeated here.

[0119] Embodiment 19 This embodiment provides a graphite negative electrode material, and its preparation method is different from that of embodiment 6 in that: The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of the external magnetic field, the current frequency of the magnetic field device is 15 Hz, the tower wall of the drying tower is ultrasonically applied and the current frequency is 45 Hz, and the granulated product is obtained by the spray drying process. The remaining method steps and the mass of the hard carbon coating layer of the obtained graphite negative electrode material and the mass of the magnetic solid particles are the same as those in Example 6 and are not repeated here.

[0120] Embodiment 20 This embodiment provides a graphite negative electrode material, and its preparation method is different from that of embodiment 6 in that: The slurry enters the drying tower of the spray drying granulation equipment through the atomizer under the action of the external magnetic field. The current frequency of the magnetic field device is 15 Hz. The tower wall ultrasound of the drying tower is turned off, and the granulated product is obtained by the spray drying process. The remaining method steps and the quality of the hard carbon coating layer of the obtained graphite negative electrode material and the quality of the magnetic solid particles are the same as those in Example 6 and are not repeated here.

[0121] Comparative Example 1 This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99 g of artificial graphite particles were added to 100 g of a phenolic resin solution having a solid content of 2% and a residual carbon content of 50%, and the mixture was stirred at a speed of 350 r / min for 90 min to obtain a slurry.

[0122] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer, the magnetic field device is turned off, ultrasound is applied to the wall of the drying tower with a current frequency of 10 Hz, and a granulated product is obtained through a spray drying process.

[0123] The prepared granulated product was added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Comparative Example 1, the SEM image of which is shown in FIG. Figure 7 shown.

[0124] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Comparative Example 1 accounts for 1% of the secondary particles having the hard carbon coating layer.

[0125] Comparative Example 2 This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99 g of artificial graphite particles were added to 100 g of a phenolic resin solution having a solid content of 2% and a residual carbon content of 50%, and the mixture was stirred at a speed of 350 r / min for 90 min to obtain a slurry.

[0126] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer, the magnetic field device is turned off, and the tower wall of the drying tower is not subjected to ultrasound, and the granulated product is obtained through the spray drying process.

[0127] The prepared granulated product was added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Comparative Example 2.

[0128] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Comparative Example 2 accounts for 1% of the secondary particles having the hard carbon coating layer.

[0129] Comparative Example 3 This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 98.5 g of artificial graphite particles were added to 100 g of a phenolic resin solution having a solid content of 3% and a residual carbon content of 50%, and the mixture was stirred at a speed of 350 r / min for 90 min to obtain a slurry.

[0130] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer, the magnetic field device is turned off, ultrasound is applied to the wall of the drying tower with a current frequency of 10 Hz, and a granulated product is obtained through a spray drying process.

[0131] The prepared granulated product was added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Comparative Example 3.

[0132] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Comparative Example 3 accounts for 1.5% of the secondary particles having the hard carbon coating layer.

[0133] Comparative Example 4 This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99 g of microcrystalline graphite particles were added to 100 g of a phenolic resin solution having a solid content of 2% and a residual carbon content of 50%, and the mixture was stirred at a speed of 350 r / min for 90 min to obtain a slurry.

[0134] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer, the magnetic field device is turned off, ultrasound is applied to the wall of the drying tower with a current frequency of 10 Hz, and a granulated product is obtained through a spray drying process.

[0135] The prepared granulated product was added into a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Comparative Example 4.

[0136] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Comparative Example 4 accounts for 1% of the secondary particles having the hard carbon coating layer.

[0137] Comparative Example 5 This comparative example provides a graphite negative electrode material, and the preparation method thereof comprises the following steps: 99 g of natural graphite particles were added to 100 g of a phenolic resin solution having a solid content of 2% and a residual carbon content of 50%, and the mixture was stirred at a speed of 350 r / min for 90 min to obtain a slurry.

[0138] The slurry enters the drying tower of the spray drying granulation equipment through the atomizer, the magnetic field device is turned off, ultrasound is applied to the wall of the drying tower with a current frequency of 10 Hz, and a granulated product is obtained through a spray drying process.

[0139] The prepared granulated product was added to a high sand kiln for carbonization at a carbonization temperature of 1150° C. for 10 hours in a nitrogen atmosphere to obtain the graphite negative electrode material of Comparative Example 5.

[0140] The mass of the hard carbon coating layer of the graphite negative electrode material prepared in Comparative Example 5 accounts for 1% of the secondary particles having the hard carbon coating layer.

[0141] Electrode sheets were prepared using the graphite negative electrode materials prepared in Examples 1 to 20 and Comparative Examples 1 to 5, and the following performance measurements were performed: initial discharge specific capacity, initial charge and discharge efficiency, and rate performance of the electrode.

[0142] The preparation method of the electrode sheet is as follows: The above-mentioned graphite negative electrode material was formulated into a slurry in a mass ratio of graphite negative electrode material: carbon black conductive agent SP: binder = 96.5:2:1.5, and mechanically stirred for 30 minutes at room temperature with a stirring speed of 2000r / min. The prepared slurry was coated on the current collector, baked in an oven at 100°C for 30 minutes, and then dried in a vacuum drying oven at 130°C for 8 hours. The prepared pole pieces were assembled into lithium-ion button batteries for constant current charge and discharge tests. The lithium sheet was used as the counter electrode, and LiPF6 was dissolved in a mixed solvent of EC / DEC / EMC=2:3:1 at a concentration of 1 mol / L to form a non-aqueous electrolyte, wherein EC is ethylene carbonate, EMC is methyl ethyl carbonate, and DEC is diethyl carbonate. The batteries were assembled in a glove box.

[0143] The test method for the first discharge specific capacity and the first charge and discharge efficiency is as follows: let the assembled button cell stand for 2 hours, discharge it to 0.005V at 0.1C, then discharge it to 0.001V at 0.09C, 0.08C, and finally 0.02C, and then charge it to 1.5V at 0.1C after standing for 10 minutes. The first week charge specific capacity / first week discharge specific capacity*100% is the first charge and discharge efficiency of the button cell tested.

[0144] The rate performance test method is as follows: let the assembled button battery stand for 2 hours, discharge it to 0.005V at 0.1C, then discharge it to 0.001V at 0.09C, 0.08C and finally 0.02C respectively, and charge it to 1.5V at 0.1C after standing for 10 minutes; let it stand for 10 minutes, charge it to 1.5V at 0.2C, and discharge it to 0.001V at 1C after standing for 10 minutes (1C discharge specific capacity / first week discharge specific capacity*100%=1C rate discharge capacity retention rate); let it stand for 10 minutes, charge it to 1.5V at 0.2C, and discharge it to 0.001V at 2C after standing for 10 minutes (2C discharge specific capacity / first week discharge specific capacity*100%=2C rate discharge capacity retention rate). The basic indicators and the results of the charge-discharge test of the artificial graphite particles, natural graphite particles and microcrystalline graphite particles used are shown in Table 1. The electrochemical performance test results of the batteries of the embodiments and comparative examples are shown in Table 2.

[0145] Table 1 Basic indicators and test results of artificial, natural and microcrystalline graphite particles

[0146] Table 2 Physical parameters and charge-discharge test results of graphite negative electrode materials prepared in different embodiments and comparative examples

[0147] The graphite negative electrode material provided in the present application includes secondary particles composed of multiple graphite particles, the graphite particles have a hard carbon coating layer and magnetic solid particles on the surface, and multiple graphite particles inside the secondary particles present a directional arrangement morphology. Although the arrangement between the active material particles of the electrode sheet prepared by using the secondary particles is still random and disordered, the degree of directional arrangement of the particles inside the active material particles is significantly improved, that is, the arrangement of the internal particles tends to be consistent or the order of the arrangement is improved (such as Figure 2 ), which can effectively shorten the transmission path of lithium ions, that is, shorten the Li + The distance to the surface of the active substance and then to the reaction center reduces the tortuosity (e.g. Figure 3 ), has the characteristics of fast ion transfer rate and multiple transfer channels, which makes the lithium-ion battery prepared by this graphite negative electrode material have high-rate performance characteristics.

[0148] The arrangement of graphite particles inside the secondary particles prepared without adding magnetic fluid is random and disordered (e.g. Figure 4 ), the tortuosity could not be reduced after it was used to prepare the electrode (such as Figure 5 ), so the rate performance is limited.

[0149] According to Table 2, the content of the hard carbon coating layer of the graphite negative electrode materials prepared in Examples 1 to 5 is consistent, but as the amount of magnetic solid particles added increases, the rate performance continues to improve, indicating that the degree of directional arrangement of the particles inside the secondary particles is improved, that is, the order of the internal particle arrangement direction is improved, which is conducive to shortening the transmission path of lithium ions, reducing tortuosity, and continuously improving the lithium ion diffusion coefficient. The amount of magnetic solid particles added in the graphite negative electrode materials prepared in Examples 6 to 8 is further increased, but the rate performance is improved slowly, indicating that the degree of directional arrangement of the particles inside the secondary particles is limited. The amount of magnetic solid particles added in the graphite negative electrode materials prepared in Examples 9 to 13 is consistent. As the content of the hard carbon coating layer continues to increase, the rate performance continues to improve, but the tapping, capacity and first effect are significantly reduced, which is not conducive to further improvement of energy density. Comprehensive performance of the graphite negative electrode material prepared in Example 6 is better in terms of capacity, first effect, tapping, rate and lithium ion diffusion coefficient.

[0150] The amount of magnetic solid particles added to the graphite negative electrode material prepared in Examples 1 to 8 is continuously increased, and the sample vibration is continuously improved, indicating that the degree of directional arrangement of the particles inside the secondary particles is improved, that is, the order of the internal particle arrangement direction is improved, resulting in improved sample vibration, which is beneficial to improve the energy density of the electrode. Among them, the amount of magnetic solid particles added to the graphite negative electrode material prepared in Examples 6 to 8 is further increased, but the vibration is slowly improved, indicating that the degree of directional arrangement of the particles inside the secondary particles is limited, which is consistent with the rate performance test results.

[0151] The test results of Example 1 and Comparative Example 1, Example 10 and Comparative Example 3, Example 14 and Comparative Example 4, and Example 15 and Comparative Example 5 indicate that the introduction of magnetic solid particles and the combination of the effect of the magnetic field can prepare secondary particles with a directional arrangement structure, that is, the order of the arrangement direction of the particles inside the secondary particles is improved or the arrangement direction tends to be consistent, which is beneficial to shortening the transmission path of lithium ions, reducing the tortuosity, and continuously improving the lithium ion diffusion coefficient, thereby improving the rate performance.

[0152] The test results of Example 6, Example 16 and Example 17 show that when the magnetic field strength is increased at the same magnetic solid particle content, the particle size decreases slightly and the rate performance is significantly improved, indicating that the degree of directional arrangement of particles inside the secondary particles is improved, that is, the order of the internal particle arrangement direction is improved, but after the current frequency is increased from 50 Hz to 90 Hz, the rate performance is improved only slightly, indicating that when the magnetic field strength is increased at a limited magnetic solid particle content, the degree of directional arrangement of particles inside the secondary particles is improved only only.

[0153] Example 6, Example 18 and Example 19 show that the greater the ultrasound, the higher the yield of the prepared negative electrode material, the less adhesion to the drying tower wall, and the less adhesion between particles. When the current frequency is increased from 25 Hz to 45 Hz, the yield improvement is limited, indicating that the continued increase in ultrasound has limited effect on the yield.

[0154] Comparative Examples 1 and 2 show that without the effect of ultrasound, the material yield is greatly reduced. Figure 8 It shows that the sample prepared in Comparative Example 2 has a large number of large particles, a larger average particle size, and a wider particle size distribution. Example 6, Example 18, Example 19, and Example 20 show that without the action of ultrasound, the sample has a large number of large particles and the yield is greatly reduced, indicating that the wall sticking phenomenon is serious, and the yield increases with the increase of ultrasound. The results of the above examples and comparative examples show that by adding a magnetic field outside the atomizer and the synergistic effect of the ultrasonic tower wall, secondary particles with a directional arrangement morphology can be prepared, with fewer large particles, more uniform particle size distribution, and high yield.

Claims

1. A graphite negative electrode material, characterized in that: It comprises a plurality of secondary particles, wherein the secondary particles are composed of a plurality of graphite particles, the surfaces of the graphite particles are coated with a hard carbon coating layer, the plurality of graphite particles are adhered together by the hard carbon coating layer, and the plurality of graphite particles are in a directional arrangement morphology.

2. The graphite negative electrode material according to claim 1, characterized in that The surfaces of the graphite particles are also coated with magnetic solid particles, and the magnetic solid particles are used to make the multiple graphite particles arranged in a directional manner under the action of an external magnetic field.

3. The graphite negative electrode material according to claim 1 or 2, characterized in that: At least one of the following conditions is met: A. The mass of the hard carbon coating layer accounts for 0.1% to 10% of the mass of the secondary particles; Preferably, the mass of the hard carbon coating layer accounts for 0.1%-3% of the mass of the secondary particles; B. The particle size D50 of the graphite particles is 3-20 μm; Preferably, the particle size D50 of the graphite particles is 5-10 μm; C. The particle size D50 of the secondary particles is 5-30 μm; Preferably, the particle size D50 of the secondary particles is 8-18 μm; D. The graphite particles are selected from one or more combinations of natural graphite, artificial graphite, expanded graphite, oxidized graphite and microcrystalline graphite.

4. The graphite negative electrode material according to claim 2, characterized in that: At least one of the following conditions is met: A. The mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~500*10 -3 %; Preferably, the mass of the magnetic solid particles accounts for 0.1*10 of the mass of the secondary particles. -3 %~200*10 -3 %; B. The magnetic solid particles are selected from one or more combinations of iron powder, ferroferric oxide, nickel magnetic beads, ferrous oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

5. A method for preparing a graphite negative electrode material, characterized in that: include: Mixing graphite particles, water-soluble resin material, and magnetic fluid to obtain slurry; The slurry is spray-dried and an external magnetic field is applied during atomization to obtain a granulated product; The granulated product is carbonized to obtain the graphite negative electrode material.

6. The method for preparing a graphite negative electrode material according to claim 5, characterized in that: At least one of the following conditions is met: A. The water-soluble resin material is selected from one or more combinations of phenolic resin, epoxy resin, furfural resin, acrylic resin, polyurethane resin, acrylic-polyurethane copolymer, furan resin, polyvinyl alcohol, chitosan, cellulose, styrene-butadiene rubber, and glucose; B. The solid content of the solution of the water-soluble resin material is 0.1% to 90%; C. The mass of the water-soluble resin material accounts for 0.1%-20% of the graphite negative electrode material; D. The magnetic fluid is a water-based magnetic fluid; E. The magnetic fluid is a water-based magnetic fluid, and the solid content of the water-based magnetic fluid is 0.001% to 50%; F. The magnetic fluid is a water-based magnetic fluid, and the particle size of the magnetic solid particles in the water-based magnetic fluid is ≤100nm; G. The magnetic fluid is a water-based magnetic fluid, and the magnetic solid particles in the water-based magnetic fluid are selected from one or more combinations of iron powder, ferroferric oxide, nickel magnetic beads, ferric oxide, carboxyl magnetic beads, amino magnetic beads, and epoxy magnetic beads.

7. The method for preparing a graphite negative electrode material according to claim 5 or 6, characterized in that: At least one of the following conditions is met: A. The graphite particles, the water-soluble resin material and the magnetic fluid are mixed to obtain a slurry, comprising: The graphite particles and the water-soluble resin material are first mixed and then a magnetic fluid is added to perform a second mixing to obtain the slurry; B. When condition A is met, the stirring speed of the first mixing is 200 r / min to 400 r / min, and the stirring time is 40 to 180 min; C. When condition A is met, the stirring speed of the second mixing is 400 r / min to 2000 r / min, and the stirring time is 40 to 180 min; D. spray drying the slurry, further comprising: applying ultrasound during drying; E. The carbonization temperature is 400°C to 1300°C; F. The carbonization time is 2 to 15 hours.

8. A negative electrode sheet, characterized in that: The invention comprises the graphite negative electrode material according to any one of claims 1 to 4.

9. A battery, characterized in that: Includes the negative electrode sheet as described in claim 8.

10. An electrical equipment, characterized in that: A battery comprising the battery of claim 9.